A modern guide to economic sociology - Zafirovski, Milan 1958- (Edward Elgar Publishing Ltd, 2020)
"This accessible guide to the rapidly growing and interdisciplinary field of modern economic sociology offers critical insights into its fundamental concepts and developments. International in scope, contributions from leading economic sociologists and sociologically-minded economists explore the intersections and implications for theory and empirical research in both disciplines. A Modern Guide to Economic Sociology positions contemporary studies in relation to earlier developments, highlighting the importance of understanding how stages of economic sociology have corresponded and converged with institutional, social, political and behavioural economics over time. Chapters offer a broad range of perspectives of topical and pressing themes including: wealth inequality, unsustainable development, ethical consumption, society and work, institutions and the economy, and society and entrepreneurship. Covering both empirical and theoretical aspects of the field, this book will benefit economic sociologists as well as economic sociology students. It will also be an important read for both economics and sociology students looking to better understand the interactions between the two fields and how they depend upon and advance one another"--..
Titel und Verantwortlichkeitsangabe der Landingpage (Elgaronline) entnommen, da kein Titelblatt vorhanden
Keywords: Wirtschaftssoziologie; Aufsatzsammlung